Does leaf rust disease matter for India’s coffee farming? Evidence and implications from a recent household survey - Narayana, M.R. (Journal of Plantation Crops, 2013)
Coffee leaf rust (CLR) is an important disease that affects Arabica coffee. Using a newly collected sample survey data of 575 Arabica coffee farmers in traditional coffee growing regions in India, this paper analyses the occurrence, awareness of field conditions for spread and severity, management practices, strategies to cope with and economic impact of CLR. Results of these analyses are surprising with strong inter-regional differences. Occurrence is universal, trend in the occurrence is non-increasing, and farmers’ awareness of the field conditions is remarkable. Recommended management practices are widely applied by planting resistant-varieties and applications of chemical sprays. Farmers’ strategies to cope with the CLR include planting new varieties, replacing coffee by other crops and selling timber. However, none of these strategies shows any appreciable impact on farmers’ income. Most surprisingly, farmers admit that CLR impacts on moderate reduction in income from Arabica coffee. These results shows that CLR does matter for coffee farming in India and its economic impact does not result in remarkable reduction in household incomes because of the effective management practices and supplementary sources of income from other crops.